A Simulation for Managing Retail Inventory Flow Using RFID and Bar Code Technology. (12th March 2021) - Atkins, Ryan; Sener, Abdurrezzak; Russo, John
ABSTRACT: The increasingly complex retail environment faces many inventory management challenges. Automatic identification and data capture (AIDC) technologies have been applied by retailers to address these challenges, with mixed levels of success. This article presents a classroom simulation of a retail environment in which students utilize a bar code scanner and a radio frequency identification (RFID) reader to manage inventory for the simulated retailer. From the simulation, students gain hands‐on experience with these technologies, learn about the advantages and disadvantages of the technologies, and discuss additional cutting‐edge AIDC technology.